A Good Death?. Issue 2 (2nd April 2016) - Cooper, Andrew
Abstract : This paper offers some personal reflections on the idea of 'a good death', a theme in the writing of philosophers since classical times. The hospice movement has made immense progress in creating conditions in which we can 'die better'. But such experiences are still the exception rather than the rule. The psychological challenge is how to relate to the dying as they are dying, and how as we die we relate to the living. I reflect on my own experience of my father's death, and a moment of fleeting but genuine contact between us. Atul Gawande's idea of the 'hard conversations' we must learn to have as we approach death are enlightening. Ultimately I argue, we die alone, and how we are, or are not, 'held in mind' as we approach death may be an index of the nearest we can approach to the idea of an 'afterlife'.